2022
DOI: 10.3390/app12136662
|View full text |Cite
|
Sign up to set email alerts
|

Textual Emotional Tone and Financial Crisis Identification in Chinese Companies: A Multi-Source Data Analysis Based on Machine Learning

Abstract: Nowadays, China is faced with increasing downward pressure on its economy, along with an expanding business risk on listed companies in China. Listed companies, as the solid foundation of the national economy, once they face a financial crisis, will experience hazards from multiple perspectives. Therefore, the construction of an effective financial crisis early warning model can help listed companies predict, control and resolve their risks. Based on textual data, this paper proposes a web crawler and textual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The readability of the text is crucial in determining whether the reader can effectively understand it [55,56]. Studies have found that the difficulty level of textual information in the annual reports of Chinese-listed companies is on par with the average of the accounting information user group.…”
Section: Sample Selection and Data Selectionmentioning
confidence: 99%
“…The readability of the text is crucial in determining whether the reader can effectively understand it [55,56]. Studies have found that the difficulty level of textual information in the annual reports of Chinese-listed companies is on par with the average of the accounting information user group.…”
Section: Sample Selection and Data Selectionmentioning
confidence: 99%
“…Textual indicators, such as managerial tone and tone indexes, are becoming more and more important parts of the process of predicting financial risk (Zhang et al, 2022). They have been cited as playing crucial roles in improving risk assessment by several academics.…”
Section: Implication Of Textual Indicators In Financial Risk Predictionmentioning
confidence: 99%
“…The investigation of user review text sentiment intensity has gained significant attention in the academic, business, and political spheres in recent years. Numerous studies have indicated the crucial role of calculating user review text sentiment intensity in optimizing domain-specific sentiment lexicons [27] and devising brand development strategies. Hence, this paper begins with user review texts and achieves precise quantification of metrics related to user attributes by computing sentiment values extracted from user reviews.…”
Section: Process 2: Quantifying the Assessment Index For Ugc Short Vi...mentioning
confidence: 99%